2022
DOI: 10.55489/njcm.1332022388
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Depression and Its Association with Geriatric Malnutrition: A Cross-Sectional Study in Hubballi, North Karnataka

Abstract: Background: The world's elderly population is increasing rapidly. According to the 2011 census elderly population contributes to 7.4% of the total population. Both physical and mental disorders are prevalent among the elderly. Symptoms of depression in older people are often overlooked and untreated. Depression leads to loss of appetite, diminution of food intake, and weight loss consequently leading to malnutrition. Methodology: A community-based cross-sectional study was conducted among the geriatric populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
2
4
1
Order By: Relevance
“…This study showed a statistically signi cant relationship between nutritional status and depression. In other words, when the older people have a favorable condition in terms of nutrition, their depression score is closer to normal, which is consistent with the results of some other studies (12,15,16). Ziaul Islam's study in Bangladesh showed that malnutrition has a strong and signi cant relationship with depression in the elderly.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This study showed a statistically signi cant relationship between nutritional status and depression. In other words, when the older people have a favorable condition in terms of nutrition, their depression score is closer to normal, which is consistent with the results of some other studies (12,15,16). Ziaul Islam's study in Bangladesh showed that malnutrition has a strong and signi cant relationship with depression in the elderly.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed a higher prevalence of depression compared to the studies conducted in China (12.2%), (2) (39) and study by Daiani and Indrawati in Indonesia (7.7%) (22). However, the prevalence of depression was lower than the studies by Nekar et al in India (68.5%) (15), the study by Rahanur Alam in Bangladesh (84%)(16), and the study by T. M. Dao in Vietnam (66.9%) (11). These discrepancies might be related to such reasons as differences in the statistical population, differences in depression screening tools and their cut-off points, regional differences, cultural differences, and the place of residence of the elderly (e.g., living at home or elderly living in nursing homes).…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Population ageing presents distinct economic challenges and geriatric health issues. 2,8 A shrinking working-age population can hinder economic growth and productivity. A smaller labour force can lead to reduced innovation, a decline in tax revenues, and an increased burden on younger generations to support the elderly.…”
Section: Implications Of Declining Fertility Ratesmentioning
confidence: 99%